Gambling Dynamism The Macao Miracle - Zheng, Victor; Wan, Po-san.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Four years after the actual implementation of its casino deregulation policy, Macao has surpassed Las Vegas as the world$1 (Bs top gambling destination in terms of annual turnover. Also, various recent surveys have put Macao at the very top of the list in terms of per capita GDP, as its economy grew shortly after the resumption of Chinese sovereignty. How could a tiny city without any natural resources on the southern coast of China have managed to achieve such a miraculous level of development? This book presents an unparalleled study of Macao$1 (Bs economic dynamism and its gambling industry not only by merging historical and current developments, but also by presenting solid subjective and objective indicators and evidence. It offers an indispensable resource for students, researchers, and general readers looking to understand Macao$1 (Bs gambling miracle.s
Preface -- Abbreviations and Acronyms -- Gambling and Society: A Theoretical Revisiting of the Issue -- Macao and Globalization: A Gambling Perspective -- The Return to Chinese Sovereignty: A Historical Turning Point -- Gambling Expansion and Economic Growth -- Gambling Expansion and Social Change -- Gambling Expansion and Political Development -- National/Regional Integration and Local Development -- The First Decade and the Road Ahead -- Chronology of Gambling Events in Macao -- Glossary.
Keywords: Culture -- Study and teaching; Economics; Management science; Cultural studies; Economics; Economics, general; Cultural Studies; Regional and Cultural Studies; Electronic books